Influence of the Computer-Aided Static Navigation Technique on the Accuracy of the Orthodontic Micro-Screws Placement: An In Vitro Study - Rodríguez Torres, Paulina Andrea; Toledano Gil, Sergio; Zubizarreta Macho, Álvaro; Bufalá Pérez, María; Riad Deglow, Elena; Tzironi, Georgia; Albaladejo Martínez, Alberto; Hernández Montero, Sofía (My University, 2021)
To analyze the influence of the computer-aided static navigation technique on the accuracy of placement of orthodontic micro-screws. One hundred and thirty-eight orthodontic micro-screws were randomly assigned to the following study groups: Group A. orthodontic micro-screw placement using a computer-aided static navigation technique (n = 69); B. orthodontic micro-screw placement using the conventional freehand technique (n = 69). In addition, the accuracy in the canine¿premolar, premolar and molar sectors was analyzed in each study group. Cone-beam computed tomography and intraoral scans were taken both prior and subsequent to orthodontic micro-screw placement. The images were then uploaded using a 3D implant planning software, where the deviation and horizontal angles were analyzed using a multivariate linear model. These measurements were taken at the coronal entry point and apical endpoint between the planned orthodontic micro-screws. In addition, any complications resulting from micro-screw placement, such as spot perforations, were also analyzed in all dental sectors. The statistical analysis showed significant differences between the two study groups with regard to the coronal entry-point, apical end-point (p < 0.001) and angular deviations (p < 0.001) between the computer-aided static navigation technique and freehand technique study groups. Moreover, statistically significant differences were showed between the different dental sectors (p < 0.001). Additionally, twelve root perforations were observed at the conventional free hand technique study group while there were no root perforations in the computer-aided static navigation technique study group. The results showed that the computer-aided static navigation technique enables a more accurate orthodontic micro-screw placement with less intraoperative complications when compared with the conventional freehand technique.
Keywords: orthodontics; micro-screws; orthodontic anchorage; mini-implants; temporary anchorage devices